Students’ acceptance and use of generative AI in pharmacy education: international cross-sectional survey based on the extended unified theory of acceptance and use of technology - Elnaem, Mohamed Hassan; Okuyan, Betul; Mubarak, Naeem; Thabit, Abrar K.; AbouKhatwa, Merna Mahmoud; Ramatillah, Diana Laila; Isah, AbdulMuminu; Al-Jumaili, Ali Azeez; Mohamed Nazar, Nor Ilyani (Springer Nature, 2025)
Background Generative artificial intelligence (GenAI) has significant potential implications for pharmacy education, but its ethical, practical, and pedagogical implications have not been fully explored.